The Implementation of Minimum Service Standard (MSS) in Health Sector at District Level and It’s Obstacles: Systematic Literature Review - Munib Arrohmah; Antono Suryoputro; Budiyono Budiyono (Postgraduate, University of Mataram, 2023)
Minimum Service Standard (MSS) in health sector is a mandatory that must be implemented by every regional government in Indonesia, so the MSS target must be 100% annually. However, the report shows that the MSS in health sector has not reached the target. National achievements in 2021 for trimesters I, II, III and IV respectively is 2.38%, 7.55%, 9.95% and 52.85%. In 2022, the achievements increased and the percentages for each trimester are 26.53%, 31.05%, 39.25% and 77.49%, but still not meet the target. This condition shows the unoptimized implementation of Minimum Service Standard (MSS) in health sector that could affected to health service delivery and society welfare. This study aims to identify the implementation and obstacles of Minimum Service Standard (MSS) in health sector at district level. This study is a systematic literature review. 9 literatures on Google Scholar database and Garuda Portal selected according PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The result shows some obstruction in the MSS in health sector’s implementation including human resources quantity and quality, inadequate infrastructure, lack of cross-sectoral and community support, and unoptimal planning and budgeting system. Based on these results it can be concluded that regional government should focused on recource factors including human recources and infrastructure, organizational factor to optimilize internal and external commitment and support including community support and budgeting support.